Advances in biocompatibility and physico-chemical characterization of microspheres for cell encapsulation - Rokstad, Anne Mari A.; Lacík, Igor; de Vos, Paul; Strand, Berit L. (Advanced drug delivery reviews, 2014)
Cell encapsulation has already shown its high potential and holds the promise for future cell therapies to enter the clinics as a large scale treatment option for various types of diseases. The advancement in cell biology towards this goal has to be complemented with functional biomaterials suitable for cell encapsulation. This cannot be achieved without understanding the close correlation between cell performance and properties of microspheres. The ongoing challenges in the field of cell encapsulation require a critical view on techniques and approaches currently utilized to characterize microspheres. This review deals with both principal subjects of microspheres characterization in the cell encapsulation field: physico-chemical characterization and biocompatibility. The up-to-day knowledge is summarized and discussed with the focus to identify missing knowledge and uncertainties, and to propose the mandatory next steps in characterization of microspheres for cell encapsulation. The primary conclusion of this review is that further success in development of microspheres for cell therapies cannot be accomplished without careful selection of characterization techniques, which are employed in conjunction with biological tests. [Display omitted]